Analysis of Guided Imagery and Music Therapy on Changes in the Intensity of Dysmenorrhea Pain in SMK Visi Global Banyuwangi - Kresna Bagus Sugiarto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Menstruation or menstruation is periodic vaginal bleeding due to the release of the uterine endometrium layer . Most women who experience dysmenorrhea overcome by taking painkillers on the market. There are several ways to reduce the pain when someone is experiencing dysmenorrhea is by engineering the pharmacological (drugs) and the technique of non-pharmacological (no drugs) such as distraction (music therapy) that can stimulate an increase in β-endorphin supplied by the body and guided imagery (guided imagery) which serves as a diversion from a painful stimulus thereby reducing the pain response. The research objective was to determine the effect of giving an guided imagery and music therapy on pain intensity changes dysmenorrhea. The research design used was True experimental . The study population was all students who had dysmenorrhea and large sample of 27 female students by using simple random sampling . Data collection using observation sheet then analyzed using Friedman test. The results showed that the significant probability value of 0.002 <0.05 means there is a significant difference between guided imagery , music therapy and control group on dysmenorrhea pain and there is a difference between before and after guided imagery on dysmenorrhea pain (p: 0,014 <0.05). There is a difference between before and after music therapy against dysmenorrhea pain (p: 0.004 <0.05). There is no difference between before and after the control group to the dysmenorrhea pain (p: 0.317> 0.05.) Among the three treatment groups most significantly affected the dysmenorrhea pain is music therapy because of its smallest significance value from the others.Based on the study, it was used as an alternative treatment in accordance with the condition of female students.